Strategi Media Sosial Instagram Dalam Membangun Customer Engangement Pengunjung di Daff Coffee Shop Kabupaten Blitar - Andiwi Meifilina (KOLONI, 2023)
The increasing number of coffeeshops in Blitar Regency certainly means that Daff coffeeshop has to maintain its business to face intense competition. Apart from that, today's consumers not only choose restaurants or coffee shops to fulfill their hunger, but also as a place to gather with friends, business colleagues, friends, family. Daff coffeeshop creates messages through marketing by posting images or videos on Instagram which can create customer engagement between producers and consumers. Customer engagement is a stage where an emotional relationship is established between the company and consumers above consumer loyalty. The reason for conducting research at Daff coffeeshop Blitar is because Daff coffee shop is the only café that offers a garden concept like a garden in your own yard and is the only café in Blitar that serves original coffee from coffee plantations in Dampit and Blitar and packaged into several types include: robusta, arabica. Daff coffee shop's foresight in maintaining its business to gain consumer loyalty is done by packaging its products, even facing the integrity of competing companies.This research uses a qualitative approach to explainapplication and descriptionsInstagram social media strategy in building customer engagement among visitors to Daff coffee shop, Blitar Regency.In this research, researchers used purposive sampling techniques. Data collection techniques were observation, interviews and documentation. The strategy for using Instagram social media at Daff Coffee Shop to obtain information, using the steps, namely: a. Determining content or topic, b. Determine the communicator, c. Determining Target Targets. Meanwhile, the Instagram social media strategy at Daff Coffee Shop processes information in composing messages and creating interesting captions, including: a. Techniques for composing messages, b. Creating captions. Then the strategy for using Instagram social media at Daff Coffee Shop to convey information, using the steps, namely: a. Selection of Posting Schedule. b. Dissemination of information, c. Feedback or feedback, d. Evaluation.The customer engagement process occurs in four stages of the engagement process which consists of interactions with consumers, including: a.Consumption, b. Curation, c.Creation